Therapeutic Potential of Oxytocin in Atherosclerotic Cardiovascular Disease: Mechanisms and Signaling Pathways - Wang, Ping; Wang, Stephani C.; Yang, Haipeng; Lv, Chunmei; Jia, Shuwei; Liu, Xiaoyu; Wang, Xiaoran; Meng, Dexin; Qin, Danian; Zhu, Hui; Wang, Yu-Feng (Frontiers in Neuroscience, 2019)
Coronary artery disease (CAD) is a major cardiovascular disease responsible for high morbidity and mortality worldwide. The major pathophysiological basis of CAD is atherosclerosis in association with varieties of immunometabolic disorders that can suppress oxytocin (OT) receptor (OTR) signaling in the cardiovascular system (CVS). By contrast, OT not only maintains cardiovascular integrity but also has the potential to suppress and even reverse atherosclerotic alterations and CAD. These protective effects of OT are associated with its protection of the heart and blood vessels from immunometabolic injuries and the resultant inflammation and apoptosis through both peripheral and central approaches. As a result, OT can decelerate the progression of atherosclerosis and facilitate the recovery of CVS from these injuries. At the cellular level, the protective effect of OT on CVS involves a broad array of OTR signaling events. These signals mainly belong to the reperfusion injury salvage kinase pathway that is composed of phosphatidylinositol 3-kinase-Akt-endothelial nitric oxide synthase cascades and extracellular signal-regulated protein kinase 1/2. Additionally, AMP-activated protein kinase, Ca2+/calmodulin-dependent protein kinase signaling and many others are also implicated in OTR signaling in the CVS protection. These signaling events interact coordinately at many levels to suppress the production of inflammatory cytokines and the activation of apoptotic pathways. A particular target of these signal events is endoplasmic reticulum (ER) stress and mitochondrial oxidative stress that interact through mitochondria-associated ER membrane. In contrast to these protective effects and machineries, rare but serious cardiovascular disturbances were also reported in labor induction and animal studies including hypotension, reflexive tachycardia, coronary spasm or thrombosis and allergy. Here, we review our current understanding of the protective effect of OT against varieties of atherosclerotic etiologies as well as the approaches and underlying mechanisms of these effects. Moreover, cardiovascular disturbances following OT application are also discussed to avoid unwanted effects in clinical trials of OT usages.